E4D Compare Software: An Alternative to Faculty Grading in Dental Education. Issue 2 (1st July 2012) - Renne, Walter G.; McGill, S. Theodore; Mennito, Anthony S.; Wolf, Bethany J.; Marlow, Nicole M.; Shaftman, Stephanie; Holmes, J. Robert
Abstract : The traditional method of evaluating student tooth preparations in preclinical courses has relied on the judgment of experienced clinicians primarily utilizing visual inspection. At times, certain aids such as reduction matrices or reduction instruments of known dimension are used to assist the evaluator in determining the grade. Despite the skill and experience of the evaluator, there is still a significant element of uncertainty and inconsistency in these methods. Students may perceive this inconsistency as a form of subjective, arbitrary, and empirical evaluation, which often results in students' focusing more on the grade than the actual learning or developing skills necessary to accomplish the preparation properly. Perceptions of favoritism, discrimination, and unfairness (whether verbalized or not) may interfere with the learning process. This study reports the use of a new experimental scanning and evaluation software program (E4D Compare) that can consistently and reliably scan a student's tooth preparation and compare it to a known (faculty‐determined) standardized preparation. An actual numerical evaluation is generated by the E4D Compare software, thereby making subjective judgments by the faculty unnecessary. In this study, the computer‐generated result was found to be more precise than the hand‐graded method.